Nonsense mutation in MERTK causes autosomal recessive retinitis pigmentosa in a consanguineous Pakistani family. Issue 8 (10th June 2010) - Shahzadi, Amber; Riazuddin, S Amer; Ali, Shahbaz; Li, David; Khan, Shaheen N; Husnain, Tayyab; Akram, Javed; Sieving, Paul A; Hejtmancik, J Fielding; Riazuddin, Sheikh
Abstract : Background: Retinitis pigmentosa (RP) is one of the most common ophthalmic disorders affecting one in approximately 5000 people worldwide. A nuclear family was recruited from the Punjab province of Pakistan to study the genetic basis of autosomal recessive RP. Methods: All affected individuals underwent a thorough ophthalmic examination and the disease was characterised based upon results for fundus photographs and electroretinogram recordings. Genomic DNA was extracted from peripheral leucocytes. Exclusion studies were performed with short tandem repeat (STR) markers flanking reported autosomal recessive RP loci. Haplotypes were constructed and results were statistically evaluated. Results: The results of exclusion analyses suggested that family PKRP173 was linked to chromosome 2q harbouring mer tyrosine kinase protooncogene ( MERTK ), a gene previously associated with autosomal recessive RP. Additional STR markers refined the critical interval and placed it in a 13.4 cM (17 Mb) region flanked by D2S293 proximally and D2S347 distally. Significant logarithm of odds (LOD) scores of 3.2, 3.25 and 3.18 at θ=0 were obtained with markers D2S1896, D2S2269 and D2S160. Sequencing of the coding exons of MERTK identified a mutation, c.718G→T in exon 4, which results in a premature termination of p.E240X that segregates with the disease phenotype in the family. Conclusion: Our results strongly suggest that the nonsense mutation in MERTK, leading to premature termination of the protein, is responsible for RP phenotype in the affected individuals of the Pakistani family.